Prioritizing psychological relief: fast-absorbing collagen sutures improve parental well-being in pediatric facial trauma care - Xie, Peili; Tan, Kaixi; Zhang, Jianfei (Frontiers in Pediatrics, 2025)
ObjectiveTo assess the psychological status and quality of life improvements in parents of children undergoing facial trauma repair emphasizing cosmetic outcomes with fast-absorbing collagen sutures, and to compare these outcomes with those in parents of children repaired with nylon sutures. A secondary objective was to compare scar outcomes between the two suture materials.MethodsFrom January 2024 to October 2024, 120 primary caregivers (defined as the parent providing ≥80% of daily wound care) of pediatric facial trauma patients were randomized into an observation group (n = 60, 7-0 fast-absorbing collagen sutures, non-removal) or a control group (n = 60, 7-0 nylon sutures, removed on day 7). Psychological assessments included the Self-Rating Anxiety Scale (SAS), Self-Rating Depression Scale (SDS), and Generic Quality of Life Inventory-74 (GQOLI-74). Scar formation was evaluated using the Scar Cosmesis Assessment and Rating (SCAR) scale at 1 month postoperatively.ResultsBaseline SAS/SDS scores and GQOLI-74 domain scores showed no intergroup differences (P > 0.05). Post-intervention, both groups exhibited reduced anxiety (ΔSAS: −12.3 ± 2.1 vs. −8.7 ± 1.8) and depression (ΔSDS: −10.9 ± 1.9 vs. −6.4 ± 1.5), with superior reductions in the observation group (P < 0.05). GQOLI-74 scores improved significantly in the observation group across all domains (psychological: 82.4 ± 5.3 vs. 75.1 ± 4.8; social: 79.6 ± 4.7 vs. 71.2 ± 4.1; P < 0.05). SCAR scores showed no significant differences between groups (3.07 ± 1.78 vs. 3.23 ± 1.64, P > 0.05).ConclusionFast-absorbing collagen sutures significantly alleviate parental anxiety/depression and improve family quality of life without compromising scar outcomes compared to nylon sutures. The non-removal protocol simplifies postoperative care, highlighting the importance of integrating caregiver psychological well-being into suture material selection.